Tanggung Jawab Hukum Platform Media Sosial terhadap Konten Pengguna di Indonesia: Potret Conditional Safe Harbor, Sistem SAMAN, dan Tarikan Menuju Akuntabilitas Proaktif - Gilang Rizki Aji Putra (UIN Jakarta, 2024)
Social media platforms have evolved from mere communication channels into digital public spheres mediating information, opinion, and expression for billions of users. The presence of illegal content—such as hate speech, pornography, disinformation, and incitement to violence—raises a fundamental question: to what extent are platforms legally responsible for user-generated content? This article analyzes Indonesia’s legal framework on platform liability, examining the intermediary liability regime, its evolution from safe harbor to conditional liability, and the implementation of the Content Moderation Compliance System (SAMAN). Using normative legal research with statutory, conceptual, and comparative approaches, the study finds that Indonesia adopts a conditional liability model requiring platforms to remove illegal content within specified deadlines upon notification, subject to administrative fines. However, regulatory fragmentation and limited due process safeguards undermine legal certainty. Comparative analysis indicates the need for stronger transparency standards and independent oversight mechanisms. Keywords: Intermediary Liability, Social Media Platforms, SAMAN, Electronic Information and Transactions Law (ITE Law), Conditional Safe Harbor, Content Moderation.